Influência da redução do tempo de tratamento térmico de homogeneização contínua na microestrutura e qualidade metalúrgica de tarugos de alumínio, liga 6063 e diâmetro de 6” - Corrêa, Renan David (Universidade Federal de São Carlos, 2014)
The homogenizing heat treatment of aluminium billets has direct influence on extrusion process productivity, surface quality and mechanical properties of extruded shapes. The homogenizing process parameters that impacts on metallurgical properties of 6063 alloys are: temperature, time and cooling rate. The maximum recommended homogenizing temperature for 6063 alloy is 590ºC. The minimum homogenizing time is 2,25h. The minimum cooling rate recommended is 400ºC/h. As for extrusion logs homogenizing process of 6063 6” diameter at Sapa Aluminium Brasil the furnace is a process bottleneck for logs production, this work has investigated about the possibility of time reducing without negative impacts on billet metallurgical properties and without detrimental impacts on productivity of extrusion process and quality of its products. This investigation was done by billet metallographic analysis, cold and hot mechanical tests and extrusion/anodizing trials for different homogenizing time conditions. The results have shown that the time reducing did not cause negative impacts for metallurgical neither for mechanical properties and because of that no detrimental effects for extrusion performance and surface finish and anodized quality was observed. Hence, was possible to decrease 20 minutes on homogenizing time and gain 14,5% of productivity on heat treatment process.
Effect of time reduction in a continuous homogenizing heat treatment on the microstructure and metallurgical quality of 6063 6 inch diameter aluminium alloy
Keywords: Metais - tratamento térmico; Liga de alumínio; Transformação de fase; Processo de extrusão; 6063 aluminium alloy; Aluminium homogenizing; Homogenizing; Aluminium extrusion billets; Al-Fe-Si phase transformation; Homogenizing time reducing; Increase homogenizing productivity; ENGENHARIAS